Land for food cultivation: is price a barrier to expansion? - Khalid, Haniza (2011)
With increasing development speculation involving farmland, total area devoted to food cultivation continues to fall, or is expected to be sold at a higher price per hectare than before. This paper compares price of land cultivated with paddy relative to other crops and proceeds to examine some unique market and institutional features of the paddy land market. A hedonic price function is estimated using land sales data (n=2222) of five types of farmland namely paddy, rubber, vacant and oil palm covering four states in the Central West coast of Peninsular Malaysia in a period of 7 years. Results show that the marginal values of land attributes included in the model (road frontage, proximity to urban centres, population growth rates, land restrictions and year of sale) vary considerably across the different categories. Mean predicted paddy land price is the lowest. The relatively cheap price and various forms of government suppost does not appear to promote expansion of paddy hectarage. Paddy farming continues to be plagued by problems related to low profit margins (low levels of re-investment), inefficient organisation of farmers and uneconomic land holdings.